Analysis of Association of Occupational Physical Activity, Leisure-Time Physical Activity, and Sedentary Lifestyle with Hypertension according to the Adherence with Aerobic Activity in Women Using Korea National Health and Nutrition Examination Survey 2016-2017 Data - Mikyung Ryu; Sol Lee; Ho Gym; Weon-Chil Baek; Heejin Kimm (International Journal of Hypertension)
Purpose. We investigated the association between occupational physical activity, leisure-time physical activity, and sedentary lifestyle with hypertension by adherence with aerobic exercise in middle-aged and elderly women. Methods. A cross-sectional analysis was performed using Korea National Health and Nutrition Examination Survey (KNHANES), a nationally representative data between 2016 and 2017. A total of 4,241 women aged 40 years or older were included. Hypertension diagnosed by physician and exercise status was asked by questionnaires. Results. Mean age of the participants was 58.4 (±11.4, range: 40∼80 years). There were 1,681 (39.6%) women in the aerobic activity adherence group. In the logistic regression analysis with adjustment for confounding factors, frequency of occupational physical activity (OPA) level (OR 1.931; p=0.048, in ≤4 per week group), walking frequency (OR 0.436; p=0.001, in 5∼7 days per week walking group compared with never walking group) in the aerobic activity adherence group, sitting hours (OR 1.849; 95% CI: 1.279–2.673, p=0.001, in 13 hours or longer group compared with 6 hours or less sitting hours group), and muscle strengthening exercises (OR 0.554; 95% CI: 0.353–0.870, p=0.010, 1∼4 days per week compared with never) in the nonadherence group were significantly associated with hypertension. Conclusions. In the aerobic activity adherence group, further research is needed to identify the influence of occupational physical activity. In the aerobic activity nonadherence group, decreasing sitting hours and increasing endurance exercise may be helpful.